Tinjauan Hukum Persaingan Usaha pada Penetapan Harga (Studi Putusan Mahkamah Agung) - Intan Wulan Sari; Mahlil Adriaman (Jurnal Ilmiah Global Education, 2026)
This study examines the application of price-fixing prohibition as regulated in Article 5 of Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, focusing on enforcement approach differences between the Business Competition Supervisory Commission (KPPU) and the Supreme Court. This research specifically analyzes Supreme Court Decision Number 1811 K/Pdt.Sus-KPPU/2022 in the PT Batik Air case and compares it with KPPU Decision Number 15/KPPU-I/2019 regarding alleged airline ticket price cartel. Using normative juridical method with statutory, conceptual, and case approaches, the results indicate that KPPU consistently applies the per se illegal approach in assessing violations of Article 5 by relying on cumulative indirect evidence. Conversely, the Supreme Court interprets the agreement element more strictly, demanding concrete proof and considering economic rationality and airline industry characteristics, thus approaching the rule of reason standard. This difference demonstrates inconsistency in evidentiary standards and interpretation of price-fixing elements, affecting legal certainty and effectiveness of competition law enforcement in Indonesia. Therefore, this study emphasizes the necessity for harmonization between KPPU and the Supreme Court to optimally achieve the objectives of Law Number 5 of 1999 in creating healthy, fair business competition and protecting public interest.